Impact of conventional and advanced cleaning techniques on the durability of firefighter turnout ensembles - Girase, Arjunsing; Thompson, Donald B.; Ormond, R. Bryan (Frontiers in Materials, 2023)
The concern for firefighters’ occupational exposure to harmful contaminants is growing due to the increase in health issues in the firefighting community. At such times, effective decontamination of personnel and equipment is an essential component of a hazard mitigation strategy. The current decontamination practices used for firefighter protective clothing have been shown to not be very effective. Hence, the scientific community is looking for several alternatives to conventional washing procedures. Liquid carbon dioxide (CO2) has been used in laundering and has distinct advantages over conventional dry-cleaning solvents such as perchloroethylene. The following study is aimed to assess how different washing procedures affect the durability of the turnout material. The study includes using three washing procedures on different samples: 1) conventional washing procedure, 2) liquid CO2 washing procedure, and 3) a high-temperature washing procedure. Samples for durability testing were constructed from a common aramid fabric used in firefighter turnout ensembles. These swatches were subjected to different washing techniques. The durability assessment was performed for physical testing of the samples, visual inspection, water repellency, and quantifying color changes using spectrophotometric analysis. The conventional wash and high-temperature washing affected the durability of the outer shell material in a significant manner. The liquid CO2 process did not affect the samples’ water repellency or physical strength. In contrast, conventional and high-temperature washing significantly affected the durability of the outer shell material. However, all samples met the criteria for tearing strength outlined in the NFPA 1971 standard subsection 7.1.11.